2014
DOI: 10.1155/2014/259238
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Alkaline-Thermostable Protease Enzyme from Pitaya (Hylocereus polyrhizus) Waste: A Potential Low Cost of the Enzyme

Abstract: The thermoalkaline protease enzyme from pitaya (Hylocereus polyrhizus) waste was purified by a factor of 221.2 with 71.3% recovery using ammonium sulphate precipitation, gel filtration, and cation exchange chromatography. Gel filtration chromatography together with sodium dodecyl sulphate gel electrophoresis (SDS-PAGE) revealed that the enzyme is monomeric with a molecular weight of 26.7 kDa. The apparent K m and V max of the protease were 2.8 mg/mL and 31.20 u/min, respectively. The optimum pH and temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…This study confirmed that having a smoke-free home policy was negatively associated with exposure to SHS in the home, which is consistent with other studies [ 18 , 19 , 20 ]. Restrictions were more common when there were no smokers in the home and when there were children present [ 14 , 21 ] especially among children less than 5 years old [ 10 ]. It is surprising that having children less than 18 was positively associated with exposure to SHS in the home, which indicates that adolescents may be seriously exposed to SHS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study confirmed that having a smoke-free home policy was negatively associated with exposure to SHS in the home, which is consistent with other studies [ 18 , 19 , 20 ]. Restrictions were more common when there were no smokers in the home and when there were children present [ 14 , 21 ] especially among children less than 5 years old [ 10 ]. It is surprising that having children less than 18 was positively associated with exposure to SHS in the home, which indicates that adolescents may be seriously exposed to SHS.…”
Section: Discussionmentioning
confidence: 99%
“…It is surprising that having children less than 18 was positively associated with exposure to SHS in the home, which indicates that adolescents may be seriously exposed to SHS. Other research has shown that having children less than 5 years of age was a correlate of having a smoke-free home policy while having children under 18 years old was not [ 10 ]. In addition, studies have shown that pregnancy and giving birth may serve as impetuses to establishing a smoke-free home [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MD simulations at 100˚C confirmed this result. This high degree of thermal stability may be beneficial in many industrial processes, for example, to decrease the risk of contamination at high temperatures and the cost of external cooling [50]. Concerning the influence of pH, protease 1147 shows approximately 80% and 50% of relative activity in pH values of 5 and 9, respectively, with good stability after 3 h of incubation at 60˚C.…”
Section: Plos Onementioning
confidence: 99%
“…It should be mentioned that thermostability of the enzyme is one of the good characteristics of the protease. In addition, thermostable enzyme can decrease the risk of contaminants at high temperature in industries and also cost of external cooling and the increased substrate solubility, allowing for higher concentrations of low solubility materials and a lower viscosity of liquids and it may also be useful in mixing (Amid, ABD Manap, & Zohdi, 2014). They can also be used to study enzyme behavior under conditions that would denature most enzymes, since enzymes resistant to heat are also, at room temperature, resistant to organic solvents, chaotropic agents, and proteolysis.…”
Section: Thermostability and Stability At Extreme Phs Of Enzymementioning
confidence: 99%